2017
DOI: 10.3389/fmicb.2017.01094
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survey Is Necessary to Reveal Various Shifts of Microbial Composition in Corals

Abstract: The coral holobiont is the assemblage of coral host and its microbial symbionts, which functions as a unit and is responsive to host species and environmental factors. Although monitoring surveys have been done to determine bacteria associated with coral, none have persisted for >1 year. Therefore, potential variations in minor or dominant community members that occur over extended intervals have not been characterized. In this study, 16S rRNA gene amplicon pyrosequencing was used to investigate the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 64 publications
5
16
0
Order By: Relevance
“…These studies were completed within a 1-year time period, yet suggested the observed changes were seasonal. The pattern from the present study instead supports the findings by Yang et al (2017), where S. pistillata also exhibited highly dynamic temporal variations in its bacterial community composition, but with little evidence of seasonal cycles over a 2-year period. Therefore, the variations in bacterial communities among time points are likely influenced by factors other than season.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These studies were completed within a 1-year time period, yet suggested the observed changes were seasonal. The pattern from the present study instead supports the findings by Yang et al (2017), where S. pistillata also exhibited highly dynamic temporal variations in its bacterial community composition, but with little evidence of seasonal cycles over a 2-year period. Therefore, the variations in bacterial communities among time points are likely influenced by factors other than season.…”
Section: Discussionsupporting
confidence: 84%
“…Variations in the coral bacterial community among time points have been suggested to reflect seasonal differences in their environment (e.g., Ceh et al, 2011; Kimes et al, 2013; Li et al, 2014; Sharp et al, 2017; Cai et al, 2018); however, all of these studies have lasted less than 1 year, which is insufficient to test hypotheses regarding seasonality. Indeed, one longer-term study (Yang et al, 2017) found the bacterial community of the brooding coral Stylophora pistillata to be dynamic, but not reflective of seasonal cycles (Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Coral-associated bacterial communities are highly diverse and dynamic [18][19][20][21]. These bacterial communities can be found in various niches associated with corals like coral mucus [22], spaces in the skeleton [23][24][25], and coral tissues [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…When the Propionibacterium sequence from this study was compared to a Propionibacterium sequence found in a coral microbiome study by Kellogg et al (2016), the sequences appeared very similar, with BLASTn sequence comparison showing a 99% identity match over 229 base pairs. Propionibacterium sequences have been reported as members of coral microbiomes by a number of studies (de Castro et al, 2010;Ainsworth et al, 2015;Kellogg et al, 2017;Yang et al, 2017). This bacterium has also been seen, via laser microdissection and fluorescence in situ hybridization (FISH), inside the coral's endosymbiotic dinoflagellates, leading Ainsworth et al (2015) to hypothesize that these bacteria may have a role in facilitating the relationship between host coral and symbiotic algae.…”
Section: Pan-species Core Microbiomementioning
confidence: 99%
“…Interestingly, this genus is also commonly associated with coral core microbiomes (Ainsworth et al, 2015;Leite et al, 2017;Yang et al, 2017) and, like Propionibacterium, has been observed within the coral's endosymbiotic dinoflagellates (Ainsworth et al, 2015). Hernandez-Agreda et al (2017) hypothesized that a Ralstonia species may play a role in carbon uptake by the host coral from the endosymbiont, based upon the localization of the bacterium in the "peri-algal space", the area within the coral that hosts the endosymbiotic algae.…”
Section: Pan-species Core Microbiomementioning
confidence: 99%